A Study on English Collocation at Sekolah Tinggi Ilmu Bahasa Asing (STIBA) Persada Bunda Pekanbaru - Lelly Zuyana Asril (STBA Prayoga Padang, 2016)
This research aimed to study about students’ understanding of English Collocation at Sekolah Tinggi Ilmu Bahasa Asing (STIBA) Persada Bunda. It was done since there were many unnatural and unacceptable words used by the students both in their conversation and writing. There are two categories of English collocation. They are grammatical and lexical collocations. The research was conducted to find which category and sub-category that were more problematic for STIBA students. There were 40 STIBA students taken as the sample of this research. The students were asked to do a test consisting of grammatical and lexicalcolloction. The aim of the test was to find out their understanding about English Collocation. The result showed that grammatical collocation was more difficult than lexical. The mean score was 11.02 : 13.55 for grammatical and lexical collocations. Grammatical mean score was lower than the other one. Besides, the students cannot answer all the questions in grammatical because the persentage was only 90 % while in lexical, the student can answer all questions perfectly (100%). Moreover the most difficult sub-category was noun + preposition with 10.7 of score. By doing more practices the students were expected to be able to increase their understanding about English Collocation.